Muslim Minoritas Dan Budaya Muslim Melayu Masyarakat Pattani Thailand Selatan - Novia Isti Setiarini (Jurnal Penelitian Agama, 2021)
Thailand, known formerly as Siam and officially as the Kingdom of Thailand, is a country in Southeast Asia. Thailand societies are dominated by Buddhist while a few moslem. The most of Muslim communities in Thailand are lived in the southern region. Five provinces habited majority moslem are Pattani, Yala, Narathiwat, some part of Satun and Songkhla. The areas are bordered Malaysia, country dominated moslem. This paper aims to know how characteristic of culture at Pattani province in Thailand. Qualitative method is used in this research. Observation, interview, and literature study are used as data collective method to get comprehensive information about the topic. Result of this research find out Culture established in southern region of Thailand has similar characteristic with culture in Malaysia country. The similarity cultures southern region of Thailand and Malaysia country are Malay language (kecek nayu); Kampong and Tengoh languages; aksara jawi; law comes from the book of fiqh; abangan and santri; education: anubban school, raudhoh, tadikayang; Islamic boarding school; clothes brackets.